Cost reduction measures in maintenance of the MPCSS class of vessels in the Royal Malaysian Navy - 233167 Jeffry Faisal; Alias Warjan, supervisor; Sekolah Pengajian Siswazah (1999)
Thesis (Sarjana Kejuruteraan (Pengurusan Kejuruteraan)) - Universiti Teknologi Malaysia, 1999